Perancangan Ulang Ruang Kelas Sekolah Dasar Pandu dengan Pendekatan Sustainable Interior Design - Rifanindio, Edwin (Waca Cipta Ruang, 2024)
ABSTRACT An eco friendly way of life that is apllied to the curriculum and infrastructure of an early childhood education institution will provide knowledge, skills and instill a caring attitude towards the environment in it’s student. Pandu School already has the concept of environment care in it’s education program, but The Pandu School elementary class room facilities are not adequate to support a safe, comfortable and enjoyable teaching and learning process atmosphere. For this reason, it is necessary to redesign elementary school classrooms so that they feel more spacious and flexible in responding to various furniture arrangements and increase the comfort of the indoor air temperature. The method uses a design method with a Sustainable Interior Design approach. The design stages start with problem formulation, data collection stage, problem formulatiom analysis, design concept stage to design creation. The redesign concept creates a safe, comfortable and pleasant interior space by making it easier for natural light and fresh air to enter the room. One side of the existing wall was opened maximally to expand the classroom floor area to make it appear more spacious while bringing an open natural atmosphere into the classroom. Keywords : Sustainable interior design , safe, comfortable, enjoyable